2002
DOI: 10.1091/mbc.01-09-0465
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Actin Rearrangement through Lysophosphatidic Acid Receptor in Neuroblast Cell Lines: Actin Depolymerization by Ca2+-α-Actinin and Polymerization by Rho

Abstract: Lysophosphatidic acid (LPA) is a potent lipid mediator with actions on many cell types. Morphological changes involving actin polymerization are mediated by at least two cognate G protein-coupled receptors, LPA 1 /EDG-2 or LPA 2 /EDG-4. Herein, we show that LPA can also induce actin depolymerization preceding actin polymerization within single TR mouse immortalized neuroblasts. Actin depolymerization resulted in immediate loss of membrane ruffling, whereas actin polymerization resulted in process retraction. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…However, while the initial hypotheses regarding LPA signaling in brain development were tested in a general sense (i.e., proliferation and nuclear movement of cerebral cortical progenitor cells), we did not examine more specific effects or other potential roles for LPA, which are likely operative, based on other studies (21,23). LPA has also been hypothesized to influence wound healing by stimulating fibroblasts to close cutaneous wounds and possibly by attracting immune system cells to the injury site (6,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the initial hypotheses regarding LPA signaling in brain development were tested in a general sense (i.e., proliferation and nuclear movement of cerebral cortical progenitor cells), we did not examine more specific effects or other potential roles for LPA, which are likely operative, based on other studies (21,23). LPA has also been hypothesized to influence wound healing by stimulating fibroblasts to close cutaneous wounds and possibly by attracting immune system cells to the injury site (6,16).…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic cerebral cortex, for example, LPA is thought to mediate numerous aspects of progenitor behavior, including proliferation and cell cycle-associated morphological changes involving process retraction and nuclear movement (19,21,23,24). In general, however, hypotheses regarding the role of LPA in cerebral cortex development have been difficult to assess due to the lack of LPA agonists and antagonists specific to each LPA receptor.…”
mentioning
confidence: 99%
“…LPA-mediated signaling has been implicated in a wide range of cell behavior, including proliferation, survival, motility, cell shape and differentiation (Anliker and Chun, 2004;Fukushima et al, 2002;Tigyi, 2001;Ye et al, 2002). Targeted mutation of LPA receptors in the mouse has shown that LPA signaling is required for normal development (Contos et al, 2000;Contos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the role of G proteins in the development of CNS, we examined the effect of agonists that are bound to GPCRs on neuronal migration. Fukushima et al (28,29) demonstrated that lysophosphatidic acid (LPA) regulates cortical neuroblast morphology and induces cluster compaction of the neuroblast cell line. They also reported that LPA inhibits neuronal migration in explant cultures and wholebrain cultures.…”
Section: Discussionmentioning
confidence: 99%